The Internationalisation of Family Firms: the Role of the Ownership Structure and the Composition of Top Management Team - Aleksandra Wąsowska (Entrepreneurial Business and Economics Review)
Objective: The objective of this paper is to investigate the determinants of family firm internationalisation, focusing on the roles of ownership (i.e. concentration of ownership, foreign ownership) and management (i.e. involvement of nonfamily managers, owner-CEO).